The role of apelinergic system in metabolism and reproductive system in normal and pathological conditions: an overview - Mehri, Keyvan; Hamidian, Gholamreza; Zavvari Oskuye, Zohreh; Nayebirad, Sepehr; Farajdokht, Fereshteh (Frontiers in Endocrinology, 2023)
Lifestyle changes have made metabolic disorders as one of the major threats to life. Growing evidence demonstrates that obesity and diabetes disrupt the reproductive system by affecting the gonads and the hypothalamus-pituitary-gonadal (HPG) axis. Apelin, an adipocytokine, and its receptor (APJ) are broadly expressed in the hypothalamus nuclei, such as paraventricular and supraoptic, where gonadotropin-releasing hormone (GnRH) is released, and all three lobes of the pituitary, indicating that apelin is involved in the control of reproductive function. Moreover, apelin affects food intake, insulin sensitivity, fluid homeostasis, and glucose and lipid metabolisms. This review outlined the physiological effects of the apelinergic system, the relationship between apelin and metabolic disorders such as diabetes and obesity, as well as the effect of apelin on the reproductive system in both gender. The apelin–APJ system can be considered a potential therapeutic target in the management of obesity-associated metabolic dysfunction and reproductive disorders.